2019
DOI: 10.1186/s12889-019-7908-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an excise tax on the consumption of sugar-sweetened beverages in young people living in poorer neighbourhoods of Catalonia, Spain: a difference in differences study

Abstract: BackgroundSugar-sweetened beverage consumption is contributing to the obesity epidemic. On 28 March 2017, Catalonia enacted a law levying an excise tax on sugar-sweetened beverages for public health reasons. The purpose of this study is to assess the impact of the tax on the consumption of sugar-sweetened beverages in Catalonia (Spain).MethodsBefore-and-after study to assess changes in the prevalence of consumption of sugar-sweetened beverages among 1929 persons aged 12 to 40 years residing in low-income neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…In California, the consumption of taxed beverages fell by 21% in the four months after the tax was implemented [51]. After one year of its introduction, the Catalonian excise tax on SSBs brought about a 39% fall in the prevalence of regular consumers of taxed beverages [52]. Also, SSB purchases decreased and water purchases increased after an SSB tax was imposed in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…In California, the consumption of taxed beverages fell by 21% in the four months after the tax was implemented [51]. After one year of its introduction, the Catalonian excise tax on SSBs brought about a 39% fall in the prevalence of regular consumers of taxed beverages [52]. Also, SSB purchases decreased and water purchases increased after an SSB tax was imposed in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the experimental purchasing tasks may not accurately reflect consumers’ behaviors in real‐world settings. Participants did not have the option to decline a purchase and they were not informed that the price increases were due to taxes; in the real world, consumers' responses to SSB taxes are often strengthened by heightened awareness as a result of media and education campaigns (6,15). Participants did not use their own money and received the product from only one task, which may have led to more carefree purchasing decisions throughout the tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, where cross-border purchases were minimal because the tax was implemented nationwide, a 7.6% decline was reported after two years of the tax [19]. Similar beverage tax in Catalonia reduced the prevalence of regular taxed beverage consumers by 39% [20]. A recent systematic review and meta-analysis of the real-world SSB tax impact found that a 10% price increase caused by the tax was associated with an average of 10% reduction in beverage purchases [21].…”
Section: Introductionmentioning
confidence: 99%